2021
DOI: 10.1111/pbi.13591
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of small molecule inhibitors of cystathionine gamma‐synthase with in planta activity

Abstract: Summary The synthesis of essential amino acids in plants is pivotal for their viability and growth, and these cellular pathways are therefore targeted for the discovery of new molecules for weed control. Herein, we describe the discovery and design of small molecule inhibitors of cystathionine gamma‐synthase, a key enzyme in the biosynthesis of methionine. Based on in silico screening and filtering of a large molecular database followed by the in vitro selection of molecules, we identified small molecules capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…The third motivation is that within the realm of PPI, those involved in the synthesis of amino acids, and in particular the essential ones for mammals, are an attractive target for the development of biosafe herbicides. Indeed, we previously showed that molecules inhibiting the methionine biosynthesis pathway are inhibitory in-planta 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third motivation is that within the realm of PPI, those involved in the synthesis of amino acids, and in particular the essential ones for mammals, are an attractive target for the development of biosafe herbicides. Indeed, we previously showed that molecules inhibiting the methionine biosynthesis pathway are inhibitory in-planta 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Interfering with the PPIs involved in the biosynthesis of essential amino acids is an attractive approach for the design of new herbicides 11 . Cysteine has a significant role in plant growth and development as it is the primary source of the sulfur moiety in sulfur-containing compounds.…”
Section: Inhibiting Protein-protein Interactions: Bringing Vast New T...mentioning
confidence: 99%